TRANSGLOBAL CAR EXPEDITION: An Unforgettable Journey - Artamonov, Maxim; Catapano , Paola; Comrie-Picard, Andrew; Devine , James; Mondardini, Rosy (GEOmedia, 2024)
Through exploration, we want to contribute to scientific knowledge and collect data that will change our understanding of the universe, engaging individuals, organizations, and people along this extraordinary journey. At a time of crucial change for our survival on the planet, we feel compelled to contribute and engineer new and brilliant solutions to keep the earth’s inhabitants healthy and human civilization to thrive.